Mid-life dementia risk scores as a predictor of CSF biomarker and cognitive response to simvastatin therapy in asymptomatic adults at risk for Alzheimer's disease: The ESPRIT trial - Marsh, Alyce J. (My University, 2010)
BACKGROOUND: Cardiovascular risk factors at mid-life are associated with an increased risk of developing Alzheimer's disease (AD). OBJECTIVE: Determine relationships between baseline dementia risk, cognitive function, CSF biomarkers, and response to simvastatin. METHODS: Middle-aged adult children of persons with AD were randomized to 9 months of 80mg simvastatin versus placebo. Statistical analysis included Spearman correlations and nonparametric modeling. RESULTS: In middle aged, asymptomatic adults at risk for AD, high dementia risk scores correlate with higher levels of CSF A-beta-40 (p=0.02), positively with Color Trials B time (r=0.355, p=<0.001), inversely with Stroop color word score (4= -0.289, p=0.0037), and positively with VSLT: Learning Score (beta=0.65, p=0.032). Low dementia risk predicts a greater decrease in CSF p-tau-181, and greater improvement in HVLT Learning Score (p=0.025) and processing speed index (p=0.005) for those on simvastatin compared to placebo. This study suggests low risk subjects benefit most from simvastatin therapy.
22 p.
Keywords: Nutritional Sciences; Biochemistry; Medicine